'Ecce homo' ou les labyrinthes de la lecture - Hervé Couchot (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics)
The motif of reading is placed at the center of Ecce Homo as both a vital problem and a practice in action. Nietzsche undertakes to reread every one of his "so good books" except the one he is currently writing, placing his reader in a position identical to his own. Faced with this ultimate Nietzschean "Library of Babel," the reader will have to re-experience for himself what it means to read his works, and assess his own reading biases in light of the ascending or declining values associated with the text. Rarely noticed by its best commentators, Ecce Homo's "abysmal" mirrored reading device is also that of a labyrinth, haunted by the figures of Ariane and Dionysus, and its singular composition combines the doctrine of eternal return with the selective experiment of reading.